Trieste Ethnographies in the Eyes of Contemporary Observers in the 19th and Early 20th Centuries - Kalc, Aleksej (Traditiones, 2024)
The paper examines how contemporary observers portrayed the ethnography of Trieste in the 19th and early 20th centuries, specifically focusing on their understanding of cultural diversity and interethnic relations. The emphasis is on nationalizing narratives from authors living in various historical contexts, offering insights into Trieste’s ethnic and national realities during a period characterized by the rise of national ideologies and polarization.